High impact running improves learning - Winter, Bernward; Breitenstein, Caterina; Mooren, Frank C.; Voelker, Klaus; Fobker, Manfred; Lechtermann, Anja; Krueger, Karsten; Fromme, Albert; Korsukewitz, Catharina; Floel, Agnes; Knecht, Stefan (Neurobiology of Learning and Memory, 2007)
Regular physical exercise improves cognitive functions and lowers the risk for age-related cognitive decline. Since little is known about the nature and the timing of the underlying mechanisms, we probed whether exercise also has immediate beneficial effects on cognition. Learning performance was assessed directly after high impact anaerobic sprints, low impact aerobic running, or a period of rest in 27 healthy subjects in a randomized cross-over design. Dependent variables comprised learning speed as well as immediate (1 week) and long-term (>8 months) overall success in acquiring a novel vocabulary. Peripheral levels of brain-derived neurotrophic factor (BDNF) and catecholamines (dopamine, epinephrine, norepinephrine) were assessed prior to and after the interventions as well as after learning. We found that vocabulary learning was 20 percent faster after intense physical exercise as compared to the other two conditions. This condition also elicited the strongest increases in BDNF and catecholamine levels. More sustained BDNF levels during learning after intense exercise were related to better short-term learning success, whereas absolute dopamine and epinephrine levels were related to better intermediate (dopamine) and long-term (epinephrine) retentions of the novel vocabulary. Thus, BDNF and two of the catecholamines seem to be mediators by which physical exercise improves learning.
Keywords: Arousal; Brain-derived neurotrophic factor; Catecholamines; Dopamine; Epinephrine; Language; Learning; Memory consolidation; Physical exercise